FUZZY LOGIC METHOD CONSIDERING COGNITIVE PROCESS FOR HUMAN RELIABILITY ANALYSIS OF SPACE LAUNCH MISSIONS - Zhao, Xianheng; Pan, Xing; Zhang, Wenjin; Lu, Xinpei (International Journal of Industrial Engineering: Theory, Applications and Practice, 2021)
Humans play an important role in operation tasks; thus, this paper has proposed a human reliability analysis (HRA) method for space launch missions. There are four performance shaping factors (PSFs) that have considerable influence on human performance based on the analysis of space launch missions. A fuzzy logic system is used as a tool to estimate the human error probability (HEP) of the missions in this study. According to the cognitive reliability and error analysis method, each PSF influences the control mode, which is used as a representation of the HEP. However, it is the cognitive process that can be directly influenced by PSFs and directly influences human performance. Therefore, it is necessary to consider the cognitive process as a part of the HRA in the field of space launch. A fuzzy logic system is used to analyze the process from PSFs to cognitive activities and then to human performance; thus, the HEP can be estimated.